Timing of Multiorgan Dysfunction among Hospitalized Infants with Fatal Fulminant Sepsis - Wynn, James L.; Kelly, Matthew S.; Benjamin, Daniel K.; Clark, Reese H.; Greenberg, Rachel; Benjamin, Daniel K., Jr.; Smith, P. Brian (American Journal of Perinatology, 2017)
Objective Identify the progression of specific signs of multiorgan dysfunction among infants with fatal sepsis.Study Design Cohort study of 679 infants who died within 3 days of the start of a late-onset sepsis (LOS) episode in neonatal intensive care units from 1997 to 2012. We extracted clinical and laboratory data on the day of death (day 0) and the preceding 5 days (days −5 to −1).Results Median (25th percentile–75th percentile) gestational age was 25 (24–28) weeks. Compared with day −1, day 0 was characterized by an increased requirement for mechanical ventilation and higher mean fraction of inspired oxygen. Measures of cardiorespiratory support and the proportion of infants with neutropenia began to rise on day −2.Conclusion Hospitalized infants with fatal LOS manifest respiratory, cardiovascular, renal, immune, and hematologic dysfunction. Knowledge of these factors and their timing may be important for the development and testing of novel therapeutics to reduce sepsis mortality.
Keywords: sepsis; infant; neonate; multiorgan dysfunction; death